Penggunaan Varian Kode Bermakna Permintaan Tolong dalam Tuturan Mahasiswa Rantau Bawean di Surabaya - Maret Arie Mashitoh; Muhammad Suryadi (Nusa: Jurnal Ilmu Bahasa dan Sastra, 2022)
The use of several languages about asking for help in the form of communication, Bawean overseas students have a worrying phenomenon about the variation of the language they use. The occurrence of variations in the language they use has an influence on the use of language. This study has a problem formulation, What is the form of the variants of languange about asking for help on Bawean overseas students in Surabaya? and What factors which influence the variants of languange used by Bawean overseas students in Surabaya. The purpose of this study is to describe the variants of asking for help languages on bawean overseas student in surabaya and the factors that influence the existence the variants of language that Bawean overseas students in Surabaya use when communicating. The method that use in this study is a qualitative descriptive method with data collection by observing and taking notes. The theory used by the researcher is code mixing by (Muysken, 2000) and code switching by (Suwito, 1983). The results showed that there were 4 variations language used by Bawean overseas students in Surabaya for asking for help, namely, Bawean language, Javanese language with Surabaya's dialect, Indonesian, and English. Factors that influence the variants of languages of bawean overseas students in Surabaya in the communication asked for help are the origin area of the speech, environmental factors, and familiarity factors.